A review of sludge characteristics in Lithuania's wastewater treatment plants and perspectives of its usage in thermal processes. (January 2017) - Praspaliauskas, M.; Pedišius, N.
Abstract: Wastewater collection and treatment, as well as the effective utilization of sewage sludge, are tasks of great importance for growing populations, rapidly developing industry and pollution reduction efforts aimed at curbing the harmful by-products generated by such processes. In this study, the current status and theory behind municipal sewage sludge disposal in Lithuania is presented. Since 2004, the country has rapidly developed its wastewater treatment system by applying contemporary technologies used in other European countries. According to statistical data, the amount of accumulated sewage sludge in the country will reach 82, 000 t/year dry weight in 2016. Of that, approximately 60% is stored in storage plants and landfills, 14% is used in agriculture, and 26% is composted. Storing such a large percentage of waste is not viable from an environmental or an economic perspective. Thermal utilization of sewage sludge is considered a promising alternative to storage, and there is strong demand for more reliable data on accruing quantities of sewage sludge and its properties, including heavy metals concentrations, at separate wastewater treatment plants. Sludge samples were collected from seven wastewater treatment plants in the cities of Vilnius, Kaunas, Klaipeda, Siauliai, Panevezys, Alytus and Silute which had populations of 528, 307, 159, 107, 97, 57 and 17 thousand inhabitants, respectively, in 2013. These cities utilized different waste water treatment technologies, and the primary industrial activities in the places selected varied. Heavy metal concentrations and ash melting temperatures were determined based on an analysis of the sludge content, and conclusions for agricultural application and energy production were made. For energy production, co-incineration with municipal waste or wood and gasification are the most reliable ways to utilize sewage sludge. Implementation of such technologies is beginning and further research into these methods is occurring at both the local and international levels.